A Handbook for Teaching and Learning in Higher Education: Enhancing Academic Practice - Edited by : Heather Fry, Steve Ketteridge & Stephanie Marshall (London Routledge Taylor & Francis Group, 2015)
"This entirely new edition of a very successful book focuses on developing professional academic skills for supporting and supervising student learning and effective teaching. It is built on the premise that the roles of those who teach in higher education are complex and multi-faceted. A Handbook for Teaching and Learning in Higher Education is sensitive to the competing demands of teaching, research, scholarship, and academic management"
Include glossary,index,illustrations
Keywords: College teaching -- College teachers -- Lecture method in teaching